THE USE OF BAR MODEL METHOD TO DEVELOP ADDITION AND SUBTRACTION WORD PROBLEM ACHIEVEMENT OF GRADE 4 BHUTANESE STUDENTS - Dolkar, Tshering; Sakulwongs, Nipaporn (Academic Journal Phranakhon Rajabhat University, 2025)
The study aimed to compare students’ achievement before and after studying through the use of the Bar model method in enhancing grade 4 students’ achievement in solving addition and subtraction word problems and their overall satisfaction with the method. The sample group was 30 students of mixed abilities and genders from a school in Samdrup Jongkhar, Bhutan and the research employed a clustered random sampling method. The instruments included structured lesson plans, pretest and posttest assessments, and semi-structured interviews. Quantitative analysis revealed a significant improvement of students’ achievements, with mean scores increasing from 12.13 (SD = 4.16) to 18.53 (SD = 3.09), a mean gain of 6.40, confirmed as statistically significant by a paired-sample t-test (p < .01). Qualitative data from the interview provided insights on students’ experiences, showing a positive reception towards the Bar model method. The students appreciated its role in enhancing collaborative learning and expressed a desire to continue using the method in future mathematics lessons. The findings indicated that the Bar Model method not only significantly improved students’ problem-solving achievements but also boosted engagement and satisfaction in mathematics learning. This results provided further evidence of an overall improvement in students’ achievements in word problems related to addition and subtraction after the use of Bar Model method.